Urban Poverty (Case Study of East Java from 2018-2022) - Alfinta Lestianpuri; Muhammad Arif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study seeks to assess how average years of schooling, job opportunities, population density, and local revenue affect poverty in nine cities within East Java Province from 2018 to 2022. The research utilizes secondary data and adopts a quantitative approach. A panel data regression method using a Fixed Effect Model (FEM) is employed. Findings indicate that average years of schooling, employment opportunities, and population density all have a significant negative impact on urban poverty. In contrast, Regional Original Income does not significantly affect urban poverty. It is crucial for the government to effectively manage local revenue to ensure equitable distribution among the population, particularly benefiting the poor.